COMPARISION OF STAND STRUCTURE AND TREE SPECIES DIVERSITY BETWEEN MEDIUM AND RICH FORESTS OF TRUONG SON FORESTRY COMPANY, QUANG BINH PROVINCE - Thi Thu Hien, Cao; Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2019)
Results from this study showed several characteristics of structure, composition and tree species diversity of the medium and rich forests in the tropical moist evergreen forests of the Truong Son Forestry Company, Quang Binh province. A total of 4 plots of 100m × 100m each placed in two forest states were surveyed and all stems ≥ 6 cm BH were measured. 3661 live stems ≥ 6 cm DBH were encountered, representing 40 families and 70 tree species. The density, mean DBH, mean height and total basal area of the medium forest ranged 809 trees/ha - 839 trees/ha, 14.55 cm – 15.05 cm, 10.80 m – 11.06 m and 19.35 m2/ha – 22.42 m2/ha, while these numbers in the rich forest were 1003 trees/ha - 1010 trees/ha, 15.55 cm – 15.64 cm, 11.79 m – 12.60 m and 28.22 m2/ha – 29.00 m2/ha, respectively. These key characteristics were significant difference between two forest states. The Exponential and Weibull distributions could provide good fit for the tree diameter and height data. The most dominant families in both two forest states were Fabaceae, Burseraceae, Lauraceae and Meliaceae, and the most important species found in both two forest states were Garuga pierrei, Ormosia balansae and Litsea glutinosa. Based on the diversity profile, there is no intrinsic diversity ordering between the medium and the rich forests.